Community Service for Naza (Delicious and Tasty) Pecel Sambal Home Industry by Mrs. Sudarwati in Gili Timur Village, Kamal Subdistrict - Mariatun, Ika Lis; Ernawati, Ernawati; Dawam, Aulia (Bisma : Bimbingan Swadaya Masyarakat, 2024)
The Community Service Program for the home industry of Sambal pecel Naza (Delicious and Delicious) in East Gili Village, Kamal District, Bangkalan Regency, is an effort to improve community welfare by processing peanuts into pecel sauce. The implementation process is in collaboration with partners engaged in the home industry business of making pecel sauce. The plan that will be carried out has three stages, namely training, mentoring, and evaluation. The training that will be carried out is in the form of training on efforts to educate and train partners to be able to develop their business. In this session, the proposing team provided training to partners and practiced developing flavor variants of pecel sauce products (sweetness, spicy taste, very spicy taste). Assistance in the use of peanut roasting machines, pecel sauce raw material grinding machines, vacuum sealer machines, and labels for the identity of the manufacturer. In addition, training in terms of marketing, attracting partners and online marketing. Furthermore, financial bookkeeping management training is simple. After the training activities, the assistance and evaluation carried out during the PKM activities continued until the partners succeeded well in developing their business